การเสริมแรงและการปรับปรุงเสถียรภาพของยางธรรมชาติโดยใช้ยางอิ่มตัวที่มีอินซิทูซิลิกา - กิตติ องค์วงศ์สกุล (จุฬาลงกรณ์มหาวิทยาลัย, 2014)
้This research studied the reinforcement of highly saturated rubbers such as ethylene propylene diene rubber (EPDM, 92.5% saturation) and hydrogenated natural rubber (HNR, 98.3% saturation) via in situ prepared by the sol-gel process using tetraethoxysilane (TEOS) as the silica precursor catalyzed by n-butylamine. In this study, the efficiency for in situ silica generation in the highly saturated rubbers was compared to the unsaturated rubber such natural rubber (NR) in terms of content and position of carbon-carbon double bonds in their structures. The morphology of rubbers containing in situ silica in terms of dispersion and particles size of in situ silica was investigated by using scanning electron microscope and transmission electron microscope, respectively. It was found that the in situ silica was agglomerated and formed the larger particles size in saturated rubber matrix. Whereas, the agglomeration of the in situ silica in the NR matrix was reduced resulting in the smaller in situ silica particles size. The optimum condition for in situ silica generation in EPDM and HNR was 96 mM n-butylamine concentration at 50 oC for 24 h to obtain the in situ silica content of 4.5 and 11.9 parts per hundred of rubber (phr), respectively. The curing characteristics, mechanical properties, thermal and ozone resistance of rubber composites between NR and EPDM or HNR with and without the in situ silica were compared with ones containing commercial silica at the same content. The results showed that the tensile strength of the rubber composite containing EPDM or HNR with in situ silica and NR at 40/60 (w/w) was 14 and 13.9 MPa respectively, which was higher than that of the rubber composite consisting of EPDM or HNR and NR or one containing the commercial silica at the similar rubber blend ratio and silica content. In addition, the results showed that the thermal and ozone resistance of rubber composite containing EPDM with in situ silica and NR were higher than that of the rubber composite containing EPDM and NR or one using the commercial silica.